Residue - McGarrity, Michael (McGarrity, Michael. Kevin Kerney novel., 2018)
"Retired police chief Kevin Kerney returns--this time as the prime suspect in a brutal cold-case murder. A long-unsolved mystery gets a grim new break when the bones of Kim Ward are unearthed in Las Cruces, New Mexico, forty-five years after her disappearance. Suspicion swiftly falls on her old college boyfriend: none other than retired police chief Kevin Kerney. The chief's hopes of clearing his name look bleak in the face of damning evidence compiled against him by State Police Lieutenant Clayton Istee--Kerney's own son. Left grasping for clues, with no alibi and not a single witness to speak for him, Kerney and his wife must race to reconstruct long-past events to identify the one person who can clear his name and expose the killer before it's too late. As their investigation unfolds, they'll discover that Kim Ward's murder isn't the only crime they'll have to solve before they can put danger behind them"--